Perfusion patterns in postictal 99mTc-HMPAO SPECT after coregistration with MRI in patients with mesial temporal lobe epilepsy. Issue 2 (1st August 1997) - Hogan, R Edward; Cook, Mark J; Binns, David W; Desmond, Patricia M; Kilpatrick, Christine J; Murrie, Vanessa L; Morris, Kevin F
Abstract : OBJECTIVES: To assess patterns of postictal cerebral blood flow in the mesial temporal lobe by coregistration of postictal 99m Tc-HMPAO SPECT with MRI in patients with confirmed mesial temporal lobe epilepsy. METHODS: Ten postictal and interictal 99m Tc-HMPAO SPECT scans were coregistered with MRI in 10 patients with confirmed mesial temporal lobe epilepsy. Volumetric tracings of the hippocampus and amygdala from the MRI were superimposed on the postictal and interictal SPECT. Asymmetries in hippocampal and amygdala SPECT signal were then calculated using the equation: % Asymmetry =100 × (right − left) / (right + left)/2. RESULTS: In the postictal studies, quantitative measurements of amygdala SPECT intensities were greatest on the side of seizure onset in all cases, with an average % asymmetry of 11.1, range 5.2-21.9. Hippocampal intensities were greatest on the side of seizure onset in six studies, with an average % asymmetry of 9.6, range 4.7-12.0. In four scans the hippocampal intensities were less on the side of seizure onset, with an average % asymmetry of 10.2, range 5.7-15.5. There was no localising quantitative pattern in interictal studies. CONCLUSIONS: Postictal SPECT shows distinctive perfusion patterns when coregistered with MRI, which assist in lateralisation of temporal lobe seizures. Hyperperfusion in the region of the amygdala is more consistently lateralising than hyperperfusion in the region of the hippocampus in postictal studies.